Optically Pumped Terahertz Molecular Laser: Gain Factor and Validation up to 5.5 THz. Issue 4 (21st January 2022) - Mammez, Marie-Hélène; Buchanan, Zachary; Pirali, Olivier; Martin-Drumel, Marie-Aline; Turut, Joan; Ducournau, Guillaume; Eliet, Sophie; Hindle, Francis; Barbieri, Stefano; Roy, Pascale; Mouret, Gaël; Lampin, Jean-François
Abstract : Quantum cascade laser‐pumped terahertz (THz) gas lasers are at the edge of revolutionizing THz science where powerful yet tunable sources have long been lacking. Maybe one of the last remaining drawbacks to a wider use of these instruments lies in the lack of available databases of potentially lasing transitions for users. A new figure of merit, the molecular gain factor is proposed, that allows to discriminate transitions by their lasing potential. Using this factor, catalogs of THz laser lines of ammonia, both 14 NH 3 and 15 NH 3, up to 10 THz are reported. Demonstration of the use of these two catalogs, and of the pertinence of the molecular gain factor, is made by experimentally observing 32 laser lines of 14 NH 3 and 5 lines of 15 NH 3 up to 5.5 THz. Prospects to generalize the use of this molecular gain factor to a wide range of molecules are discussed. Abstract : A figure of merit, the molecular gain factor G m, is established. It allows to compare the lasing potential of the possible laser transitions of molecular species used as gain medium for optically pumped molecular lasers. This factor has enabled a straightforward observation of ammonia laser lines up to 5.5 THz.